The Evolution of a Specialised Practice: Consulting and Contracting in the Integrated Envelope Delivery Industry. (2nd March 2020) - Simmons, Marc
Abstract: In the last two decades the traditional relationship between architects and contractors has changed. Headquartered in Brooklyn, New York, Front, who specialise in building envelopes, have consistently blurred these supposed boundaries to achieve the high‐performance facades on some of the most iconic architecture of these years. Front co‐founder Marc Simmons explains these fluxing relationships and their holistic design benefits.